A Likely Role for a Novel Cell Therapeutic Target of Transforming Growth Factor-β1 on Radiation Pneumonitis in Lung and Nasopharyngeal Cancer Patients. (6th April 2020) - Yin, Qin; Zhu, Bing; Zhang, Jixian; Yu, Yihan; Li, Pengcheng
The association between the polymorphism of transforming growth factor (TGF)-β1 and risk of radiation pneumonitis has been extensively investigated; however, conclusive results were unavailable. Eligible studies were identified from the database of Medline, Web of Science, EMBASE, and CNKI (China Knowledge Resource Integrated Database) up to September 2019. The odds ratio (OR) and 95% confidence interval (95% CI) were used to assess the strength of the relationship. The results showed that there were associations between TGF 869 T/C (rs1982073) and risks of radiation pneumonitis. Subgroup analyses showed that TGF 869 T/C was associated with risk of radiation pneumonitis in Caucasians (OR [95% CI]: 0.45 [0.31 to 0.67] for C carriers vs. TT). In addition, subgroup analyses also suggested that the C allele was associated with decreased risks of radiation pneumonitis among hospital-based case–control studies (0.56 [0.39 to 0.82] for C carriers vs. TT). Meanwhile, C allele was also suggested to be associated with decreased risk of radiation pneumonitis among PCC (0.60 [0.38 to 0.96] for C carriers vs. TT). Especially, C allele was also found to be associated with decreased risk of radiation pneumonitis from the participants with lung cancer (0.57 [0.37 to 0.90] for C carriers vs. TT). Our meta-analysis shows that T allele in TGF 869 T/C is significantly associated with the increased risk of radiation pneumonitis, especially for Caucasians, and for the participants with lung cancer.